PERAN STRATEGI STAKEHOLDER DALAM PENINGKATAN MUTU PENDIDIKAN DI SD NO 1 KUTUH - Ida Bagus Gede Surya Abadi; Chindytia Chindytia; Ni Komang Hany Trisia Dinda Rani; Ni Kadek Mona Prawistya Giri; Ni Putu Diandra Paramitha Dirgantara (STKIP Pesisir Selatan, 2026)
This research was motivated by the importance of stakeholder involvement in improving the quality of education through collaborative and participatory school management. The study aimed to describe the strategic role of stakeholders in improving educational quality at SD No. 1 Kutuh. This research used a qualitative approach with a descriptive type. Data were obtained through observation, interviews, and documentation, then analyzed using an interactive analysis model consisting of data reduction, data presentation, and conclusion drawing. The results showed that stakeholders, including the principal, teachers, educational staff, parents, school committees, communities, and students, played strategic roles in supporting educational quality improvement. The principal acted as a participatory leader, teachers contributed to learning and character building, educational staff supported school administration, while parents, committees, and communities became strategic partners in supporting school programs. The collaboration among stakeholders created an effective, participatory, and sustainable educational environment. Therefore, stakeholder synergy plays an important role in improving the quality of education at school.